2010
DOI: 10.1016/j.jiph.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a school-based program for diagnosis and treatment of latent tuberculosis infection in immigrant children

Abstract: Sociocultural and behavioural factors are involved in acceptance of LTBI treatment in, immigrant children. Adherence to treatment is challenging and requires comperhension of sociocultural beliefs and accessibility to TB clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…Absence of positive TST reactions in our study strengthens the inference that BCG is not interfering with TST interpretation even though 86.11% (155/180) of participants had already been vaccinated against TB with BCG around pre-school ages. Similar related finding we rerecorded by Minodier et al (2010) [20], namely that a positive TST is more likely to be related to an increased duration of TB exposure in the TB-endemic country of birth rather than to previous BCG vaccination.…”
Section: Discussionsupporting
confidence: 85%
“…Absence of positive TST reactions in our study strengthens the inference that BCG is not interfering with TST interpretation even though 86.11% (155/180) of participants had already been vaccinated against TB with BCG around pre-school ages. Similar related finding we rerecorded by Minodier et al (2010) [20], namely that a positive TST is more likely to be related to an increased duration of TB exposure in the TB-endemic country of birth rather than to previous BCG vaccination.…”
Section: Discussionsupporting
confidence: 85%
“…Increased age was also found to be significantly associated with a positive TST in majority of the studies [23-26, 42, 45, 49, 50, 55]. Age was not significant in 4 studies [27,35,36,67] although two studies [35,36] were performed in subjects\18 years old and therefore were not able to look at older age categories. Male gender was not found to be significantly associated with IGRA positivity in three studies [60,63,65], however two concluded significant association [58,62].…”
Section: Predictors Of Ltbi Screening Test Positivitymentioning
confidence: 99%
“…Test Positivity in Immigrants: Country of Origin When using a cut-off of\30 per 100,000 population as low TB incidence, we found 5 TST studies [35,36,44,50,51] and 1 IGRA study [64], using the QFT-GIT, which examined prevalence of positive tests by TB incidence in country of origin (Table 4). A total of 5,207 immigrants from low TB incidence countries and 21,513 immigrants from high TB incidence countries had TST results, with a total of 1,331 (25.6 %) and 8,924 (41.5 %) of immigrants from low incidence and high incidence countries being TST positive, respectively.…”
Section: Studies Evaluating Prevalence Of Ltbi Screeningmentioning
confidence: 99%
“…Minodiera et al [12] evaluated a 10-year school-based latent TB infection screening programme, in which 4375 children were offered screening, 82.3% of them consented to have undergone the tuberculin skin test, and 22.8% were positive. One study concerning children aged 15 years and younger found a variable progression risk: the highest was in children between birth and 12 months of age, and the risk for children aged between 1 and 5 years and teenagers decreases [21].…”
Section: Introductionmentioning
confidence: 99%